HYDROPHYTE DIVERSITY OF RAWANWADI LAKE , DISTRICT BHANDARA, MAHARASHTRA STATE, INDIA (International Journal of Food and Nutritional Sciences, 2022)
Hydrophytes play an important role in maintaining aquatic biodiversity. Hydrophytesoffer habitats suitable for supporting growth of a variety of aquatic life forms. The present studyemphasized on the preliminary assessment of hydrophytes diversity of Rawanwadi lake ofBhandara district, Maharashtra, India. A well planned survey was carried out frequently for aperiod of one year January 2023 to January 2024.Rawanwadi Lake is situated near Wakeshwar village on Bhandara –Paoni road.Wevisited in different season to study the biodiversity of aquatic, marshy and wetland plants.During study,total 26 species ofhydrophytes were recorded. These species belongs to 23 generaand 19 families. Among these 6 species are submerged hydrophytes, 5 species are free floating,5 species are rooted floating and 10 species are emergent.The present work exhibited the database of hydrophytes in Rawanwadilake which willhelp in future work for its conservation, preservation and addition of the local biodiversity